God dwells among us : a biblical theology of the temple - Beale, G. K. (Gregory K.), 1949-; Kim, Mitchell (Downers Grove IVP Academic, 2014)
"What does the temple mean for the church's ongoing mission in the world? This ESBT volume examines temple theology throughout Scripture, exploring how this theme relates to Christian life and witness today. God has always desired to dwell among us; now the church must follow its missional call to extend the borders of God's Kingdom and take his presence to the ends of the earth"--
Includes bibliographical references (pages [157]-162) and indexes.
Keywords: Bible -- Theology; Presence of God; Temple of God; Eden